Differences in Influenza-Specific CD4 T-Cell Mediated Immunity Following Acute Infection Versus Inactivated Vaccination in Children - Shannon, Ian; White, Chantelle L; Yang, Hongmei; Nayak, Jennifer L (The Journal of infectious diseases, 2021)
Abstract Background Early childhood influenza infections imprint influenza-specific immune memory, with most studies evaluating antibody specificity. In this study, we examined how infection versus inactivated influenza vaccination (IIV) establish pediatric CD4 T-cell mediated immunity to influenza and whether this poises the immune system to respond differently to IIV the following year. Methods We tracked influenza-specific CD4 T-cell responses in 16 H3N2 infected and 28 IIV immunized children following both initial exposure and after cohorts were revaccinated with IIV the following fall. PBMCs were stimulated with peptide pools encompassing the translated regions of the H3 HA and NP proteins and were then stained to assess CD4 T-cell specificity and function. Results Compared to IIV, infection primed a greater magnitude CD4 T-cell response specific for the infecting HA and NP proteins, with more robust NP-specific immunity persisting through year 2. Post infection, CD4 T cells preferentially produced combinations of cytokines that included interferon-γ. Interestingly, age-specific patterns in CD4 T-cell reactivity demonstrated the impact of multiple influenza exposures over time. Conclusions These data indicate that infection and vaccination differentially prime influenza-specific CD4 T-cell responses in early childhood, with these differences contributing to the lasting immunologic imprinting established following early influenza infection. Clinical Trials Registration NCT02559505. In this study, influenza-specific CD4 T-cell responses were compared in children either acutely infected with influenza or vaccinated with IIV. H3- and NP-specific CD4 T-cell reactivity was found to vary depending on both subject exposure history and age.